Replacement names for Eutrigaster (Graffia) Csuzdi & Zicsi, 1991 and Dichogaster (Malawia) Csuzdi, 2010 (Oligochaeta, Acanthodrilidae) - Csuzdi, Csaba (Zootaxa, 2014)
The earthworm genus Eutrigaster Cognetti, 1904 has long been in synonymy with Dichogaster Beddard, 1888 until Sims (1987) resurrected it for the Central American Dichogaster-like species possessing a muscular proventriculus in segment 5. Today the genus consists of some 50 species distributed in two subgenera (Csuzdi 2012). The subgenus Eutrigaster (Graffia) Csuzdi & Zicsi, 1991 was erected for species that differ from the type species of the genus in possessing penial setae. According to the summary by Fragoso & Brown (2007) the subgenus Graffia contained 27 taxa. Later, further three species were described (Sherlock et al. 2011; Sherlock & Csuzdi 2013). However, the subgenus name Graffia is a junior homonym of the turbellarian genus Graffia Levinsen, 1879. (A further junior homonym Graffia Ihering, 1880 (Platyhelminthes: Turbellaria) has already been renamed as Graffilla Ihering, 1880). Here the replacement name Eutrigaster (Graffiona) nom. nov. is proposed for the earthworm subgenus Eutrigaster (Graffia).